1986
DOI: 10.1136/oem.43.6.363
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality in the British rubber industry: 1946-80.

Abstract: Although it is over 30 years since an excess of bladder cancer was first identified in British rubber workers, the fear has persisted that this hazard could still be affecting men working in the industry today. Furthermore, suspicions have also arisen that other and hitherto unsuspected excesses of cancer might be occurring. For these reasons 33 815 men, who first started work in the industry between 1 January 1946 and 31 December 1960, have been followed up to 31 December 1975 to ascertain the number of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…The influence of vulcanization gases and rubber fumes on lung cancer risk has been described by British researchers (7). As was shown by our hygienic studies, the highest concentrations of benzo[a]pyrene, sometimes exceeding the occupational exposure limit of 0.15 ug .…”
Section: Discussionsupporting
confidence: 53%
“…The influence of vulcanization gases and rubber fumes on lung cancer risk has been described by British researchers (7). As was shown by our hygienic studies, the highest concentrations of benzo[a]pyrene, sometimes exceeding the occupational exposure limit of 0.15 ug .…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, the observed differences in DNA adduct levels by production functions were comparable to the distribution of the urinary bladder cancer risk in the past. Urinary bladder cancer risk was then observed in various work areas but mostly in the compounding and mixing departments [Parkes et al, 1982;Sorahan et al, 1986], which suggests that the observed DNA adducts in this study might be related to exposure to one or more constituents of raw rubber chemicals, carbon black, or process oils used within the rubber industry. Only structural characterization of the detected DNA adducts, however, could have given more insight into the chemical origin of these DNA adducts.…”
Section: Discussionmentioning
confidence: 76%
“…We did not include unpublished data and studies reported only as abstracts. We identified 12 cohort studies from nine countries examining distinct populations of workers in the rubber industry [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] ; seven nested casecontrol studies in this industry [34][35][36][37][38][39][40] ; 48 distinct community based case-control studies from 16 countries that used questionnaire data and reported risks for employment in the rubber industry ; and finally, 23 studies based on administrative data -such as death certificates, cancer registration, or linkage between census and cancer registry-that presented results by industry or occupation pertinent to assess the risk of cancer among rubber workers. Some of the studies reviewed are updates or more specific investigations of previously reported cohorts.…”
Section: Methodsmentioning
confidence: 99%